The Effect of Superabsorbent Polymer and Nano-Silica on the Properties of Blended Cement - Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Incorporating superabsorbent polymer (SAP), which has the abilities of absorption and desorption in cement mortar, can achieve the effect of internal curing. It is expected that the incorporation of nano-silica will improve the workability and strength in cement mortar/concrete. Hence, this study aims to examine the effect of SAP and nano-silica on the properties of blended cement paste. The experimental investigations via several tests such as consistency, setting time, compressive strength, UPV, and acid test were performed. Based on energy-dispersive X-ray analysis (EDX) test and scanning electron microscopy (SEM) test results, the morphology of hydration products and mineral compositions of cement paste were further analysed, and the mechanism of SAP with 0.2% and 0.3% and NS with lower percentages ranging from 0.5% to 2% on the performance of cement paste was studied. The results exhibited that incorporating SAP in various percentages from 0.5% to 2% prolonged the initial setting time, reduced the fluidity, and increased the water content and formation of pores. In addition, various percentages ranging from 0.5% to 2% of NS were added; thereby, an increase in the hydration process and refining the microstructure was found. The microscopic test results showed that the blended cement paste can effectively improve the denser microstructure and refine the pore structure. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.